Local Authority-Level Source Apportionments of PM2.5 Concentrations based on the CAPSS 2016: (VIII) Busan and Gyeongnam 2016년 국가배출목록 기반 기초 지자체별 초미세먼지 기여도 분석: (VIII) 부산, 경남 - Kang, Yoon Hee; You, Seunghee; Kim, Eunhye; Bae, Minah; Son, Kyuwon; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2021)
In this study, source-contributions on PM2.5 concentrations in five regions of Busan and eighteen local authorities of Gyeongnam was estimated with the Comprehensive Air quality Model with eXtensions with Particulate Source Apportionment Technology (CAMx-PSAT) for the whole year of 2016. The domestic contributions to the annual mean PM2.5 concentrations in Busan and Gyeongnam were 8.5 μg/m3 and 7.5 μg/m3, respectively. In Gyeongnam, the provincial selfcontribution to the annual mean PM2.5 was the higher (2.8 μg/m3) than that from the individual neighboring province. The contribution of Jeonnam, Gyeongbuk, Chungnam, and Ulsan to the annual mean PM2.5 in Gyeongnam were 1.2, 0.8, 0.6, 0.5 μg/m3, respectively. In Namhae-si and Hadong-gun, locating in the western part of Gyeongnam and adjacent to Jeonnam, the contributions of Jeonnam to the PM2.5 concentrations were higher than the provincial self-contribution. In Busan, the provincial self-contribution to the annual mean PM2.5 was 3.4 μg/m3. In particular, the self-contribution in the central western region, where Busan port is located, was highest among the five regions in Busan. However, the over-predicted NO2 and SO2 concentrations in this region can be in part due to the overestimations of NO2 and SO2 emissions used in this study (i.e., Clean Air Policy Support System 2016). Among the neighboring provinces, the contribution of Gyeongnam showed the highest to annual mean PM2.5 in Busan for the year, followed by Ulsan, Gyeongbuk, and Chungnam. In Busan, the control measures on the Primary PM2.5 emissions are recommended to mitigate the PM2.5 concentrations due to the high emission-toconcentration conversion rate and the self-contribution.
Keywords: Busan; Coastal region; Gyeongnam; Neighboring provincial contributions; Pm2.5; Self-contribution